2012
DOI: 10.1080/10926488.2012.656255
|View full text |Cite
|
Sign up to set email alerts
|

Who's Missing the Point? A Commentary on Claims that Autistic Persons Have a Specific Deficit in Figurative Language Comprehension

Abstract: It’s become a caricature of autistic persons that they don’t understand figurative language. Despite empirical evidence to the contrary, three of the four contributions to this special issue endorse this stereotype without question. And all four contributions attribute this supposed deficit to even shakier fallacies, such as the controversial claim that autistic people lack empathy or a ‘theory of mind.’ In this commentary, we begin by reviewing the literature more exhaustively than the other contributions, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
3
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 91 publications
6
86
3
4
Order By: Relevance
“…Additionally, children with ASD (especially those with good syntax abilities) were able to benefit from the use of context in understanding unfamiliar idiomatic phrases (Norbury, 2004). This line of research overall suggests that some children with ASD may not show impairments in pragmatic language or nonliteral language if they show significant progress in the development of their basic language abilities (Gernsbacher & Pripas-Kapit, 2012;Norbury, 2004Norbury, , 2005Whyte et al, 2014). Thus, understanding the role of expressive vocabulary and syntax abilities in supporting the development of pragmatic language and nonliteral language may be important for choosing appropriate matching variables to prevent biased conclusions about the nature of language abilities for individuals with ASD.…”
Section: Factors Supporting Developmentmentioning
confidence: 91%
See 3 more Smart Citations
“…Additionally, children with ASD (especially those with good syntax abilities) were able to benefit from the use of context in understanding unfamiliar idiomatic phrases (Norbury, 2004). This line of research overall suggests that some children with ASD may not show impairments in pragmatic language or nonliteral language if they show significant progress in the development of their basic language abilities (Gernsbacher & Pripas-Kapit, 2012;Norbury, 2004Norbury, , 2005Whyte et al, 2014). Thus, understanding the role of expressive vocabulary and syntax abilities in supporting the development of pragmatic language and nonliteral language may be important for choosing appropriate matching variables to prevent biased conclusions about the nature of language abilities for individuals with ASD.…”
Section: Factors Supporting Developmentmentioning
confidence: 91%
“…For TD children, there is some evidence that language abilities develop together in parallel, with basic language abilities (such as vocabulary) correlating strongly with nonliteral language abilities (Johnson, 1991;Rundblad & Annaz, 2010a). Research suggests that understanding of nonliteral language is supported by the ability to use the linguistic and social context to abstract meaning, and that vocabulary and syntax abilities are likely to support this process (Gernsbacher & Pripas-Kapit, 2012;Rundblad & Annaz, 2010a;Vosniadou, 1987). With regard to pragmatic language, Volden et al (2009) found that a composite of expressive and receptive basic language abilities predicted a large portion of the variance in pragmatic language ability for children with ASD.…”
Section: Factors Supporting Developmentmentioning
confidence: 94%
See 2 more Smart Citations
“…The figurativeness of non-literal language inspired researchers to use metaphors (Aziz-Zadeh et al, 2006) and idioms (Boulenger et al, 2009) as stimuli to investigate motor semantics. The ability to comprehend non-literal language is impaired in a number of clinical populations (Gernsbacher and Pripas-Kapit, 2012;Thoma and Daum, 2006), including patients with schizophrenia (Rapp, 2009;Rapp and Schmierer, 2010), autistic subjects (Martin and McDonald, 2004), and patients with dementia (Rapp and Wild, 2011) or other neurodevelopmental disorders (Annaz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%